2018
DOI: 10.5194/acp-18-4817-2018
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbon energy generates public health savings in California

Abstract: Abstract. California's goal to reduce greenhouse gas (GHG) emissions to a level that is 80 % below 1990 levels by the year 2050 will require adoption of low-carbon energy sources across all economic sectors. In addition to reducing GHG emissions, shifting to fuels with lower carbon intensity will change concentrations of short-lived conventional air pollutants, including airborne particles with a diameter of less than 2.5 µm (PM 2.5 ) and ozone (O 3 ). Here we evaluate how business-as-usual (BAU) air pollution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…The BAU 8 hr max average surface O 3 concentration reaches a maximum of 41.85 ppb in Southern California downwind (east) of LA with increases of 2–4 ppb in northern California and LA under the GHG‐Step scenario. These surface concentration changes are consistent with previous simulations using a stand‐alone regional chemical transport model (Zapata et al, 2018b). Decreasing NO x emissions in the GHG‐Step scenario lead to increasing O 3 concentrations because the BAU scenario had excess NO x that quenched O 3 formation.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The BAU 8 hr max average surface O 3 concentration reaches a maximum of 41.85 ppb in Southern California downwind (east) of LA with increases of 2–4 ppb in northern California and LA under the GHG‐Step scenario. These surface concentration changes are consistent with previous simulations using a stand‐alone regional chemical transport model (Zapata et al, 2018b). Decreasing NO x emissions in the GHG‐Step scenario lead to increasing O 3 concentrations because the BAU scenario had excess NO x that quenched O 3 formation.…”
Section: Resultssupporting
confidence: 92%
“…The altered marine emissions increase surface PM 2.5 EC by as much as +0.62 μg m −3 (Figure 2d), surface PM 2.5 sulfate by +0.29 (Figure 2j), surface PM 2.5 OC by +0.13 μg m −3 (Figure 2f), and surface PM 2.5 nitrate by +0.04 μg m −3 (Figure 2h) over the shipping lanes. Increased use of biofuels over land is an economically optimal way to use the limited quantity of biofuels for maximum GHG emissions reductions in the GHG‐Step scenario (Zapata et al, 2018a, 2018b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The avoided all-cause mortality incidence associated with reductions in long-term PM 2.5 exposure was estimated based on pooling log-linear CRF estimated by Jerrett et al and Jerrett et al (California studies), and the kriging and land use regression results are obtained from Krewski et al (US study). While log-linear CRFs were selected for consistency with several recent studies, ,,, it has been suggested that log–log supralinear CRFs (i.e., an upward curving slope) may be more appropriate for estimating mortality incidence at lower PM 2.5 concentrations. , Therefore, avoided mortality incidences are also estimated using the supralinear CRF from Burnett et al (global study) . Relative to the results for log-linear CRFs, 46–57% increases in health benefits are estimated with the increasing difference between supralinear and linear CRF estimations, as the standard is reduced, which agrees with the findings of Marshall et al…”
Section: Methodsmentioning
confidence: 99%